FGF1 improves functional recovery through inducing PRDX1 to regulate autophagy and anti‐ROS after spinal cord injury. Issue 5 (7th March 2018) - Li, Jiawei; Wang, Qingqing; Cai, Hanxiao; He, Zili; Wang, Haoli; Chen, Jian; Zheng, Zengming; Yin, Jiayu; Liao, Zhiyong; Xu, Huazi; Xiao, Jian; Gong, Fanghua
Abstract: Fibroblast growth factor 1 (FGF1) is thought to exert protective and regenerative effects on neurons following spinal cord injury (SCI), although the mechanism of these effects is not well understood. The use of FGF1 as a therapeutic agent is limited by its lack of physicochemical stability and its limited capacity to cross the blood‐spinal cord barrier. Here, we demonstrated that overexpression of FGF1 in spinal cord following SCI significantly reduced tissue loss, protected neurons in the ventricornu, ameliorated pathological morphology of the lesion, dramatically improved tissue recovery via neuroprotection, and promoted axonal regeneration and remyelination both in vivo and in vivo. In addition, the autophagy and the expression levels of PRDX1 (an antioxidant protein) were induced by AAV‐FGF1 in PC12 cells after H2 O2 treatment. Furthermore, the autophagy levels were not changed in PRDX1‐suppressing cells that were treated by AAV‐FGF1. Taken together, these results suggest that FGF1 improves functional recovery mainly through inducing PRDX1 expression to increase autophagy and anti‐ROS activity after SCI.